Microstructure and superconducting properties of Y-Ba(Ca/K)-Cu-O (Y-123 and Y-358) systems synthesized using thermal treatment method - Dihom, Mustafa Mousa Ali (2018)
There is a lack of reports on superconducting behavior of Y3Ba5Cu8O18-δ (Y-358) superconductor which belong to Y-Ba-Cu-O family. In addition, the role of alkali metals, Ca and K, substitution on the Ba site on the microstructural property of Y-Ba-Cu-O superconductors have not been well understood. In this work, bulk Y-358 and YBa2Cu3O7-δ (Y-132) superconductors were synthesized by a new technique based on thermal treatment method using PVP as capping agent. The samples were sintered in flowing O2 at 980°C for 24 hour. In addition, the effect of alkali metals (M = Ca and K) substitutions in Ba site of Y-123 and Y-358 on the microstructure and superconducting properties were systematically investigated using X-rays diffraction (XRD), field emission scanning electron microscope (FESEM), energy-dispersive X-ray spectroscopy (EDX), resistivity behaviour (ρ–T), temperature dependence of resistance measurement, and alternating current susceptibility (AC) and electron spin resonance (ESR) techniques. From XRD results, the Y-123 and Y-358 showed orthorhombic crystal structure besides small amount of secondary phased such as Y-211. In the case of Y-123, the orthorhombicity and crystallite size changed differently with Ca and K substitutions. For Ca substituted Y-358, the orthorhombicity and crystallites size increases up to x = 0.01 and 0.02 respectively and then decreases. The intensity of XRD peaks changed unsystematically with K substitution in Y-358, however it shows improvement at x = 0.03 and 0.14. From Field Emission Scanning Electron Microscope (FESEM) micrographs, the grain size of pure Y-358 is larger and more compact compared to Y-123. The grain size was found to be larger when Ba is substituted with either Ca or K than the pure samples in both Y-123 and Y-358. For both Y-123 and Y-358 samples, the grains become much finer, almost with different shape and well-connected as K contents increases. Both Y-123 and Y-358 samples exhibited good metallic behaviour in the normal state and one step transition. The Y-123 and Y-358 showed critical temperature Tc(R=zero) at 87 and 92 K and onset of superconducting transition Tc (onset) at 93 K and 98 K, respectively. The Tc(R=zero) for Ca substituted Y-123 and Y-358 was decreased. The changing of lattice parameters in Y-123 and Y-358 structure due to Ca substitution may disturb the oxygen content and hence affect Tc. The Tc(R=zero) was increased as K substitution in Y-123 increased. In general Y-123 and Y-358 samples with initial Ca and K substitution show sharper superconducting transition (Tc) than pure, which could be due to good microstructural morphology and better crystallinity. The AC susceptibility measurement show that for the Ca substituted Y-123 and Y-358 samples a decrease in diamagnetism onset temperature Tc-onset, was observed from real part (χ') which exhibited two-step transitions related to the superconducting intra and intergrain coupling. The Tc-onset decreased in the case of Ca substituted samples and increased in the case of K substituted samples. This decrease is mainly due to the decrease and increase of hole concentration respectively. The intergranular critical current density, Jcm, of pure Y-123 and Y-358, 34.4 A cm-2 and 34.7 A cm-2 respectively, increased to 35 Acm-2 at (x=0.08) and 36.3 Acm-2 at (x=0.2) for Ca substituted Y-123 and Y-358, respectively and K to 35 Acm-2 at (x=0.1) and 38.8 Acm-2 at (x=0.12) for Ca substituted Y-123 and Y-358, respectively, which could be due the improvement of the grain boundary and the hence the grains’ coupling. On the other hand, Josephson current, Io, and Josephson energy, Ej decreased and increased with the Ca and K concentration respectively due to degrading and coupling between the grain connectivity. From electron spin resonance (ESR), the Ca and K substituted in Y-123 and Y-358 showed ESR spectra consisted of two peaks. The g-factors increased with increment of Ca and K content in both Y-123 and Y-358 samples, which could be due to changes in the oxygen ordering in Y-123 and Y-358.